2008
DOI: 10.2460/javma.232.8.1193
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prognostic factors associated with injection-site sarcomas in cats: 57 cases (2001–2007)

Abstract: The development of distant metastasis, which may occur later during the course of the disease, was identified as a prognostic factor for overall survival time in cats with ISSs. In addition, cats with histologic grade 3 ISSs should be considered for further interventional studies with chemotherapy to prevent the high rate of distant metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
115
2
14

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(141 citation statements)
references
References 27 publications
10
115
2
14
Order By: Relevance
“…Fortunately, the situation in Poland is better than, for example, in the UK where the most affected site is still the interscapular region and the percentage of FISS arisen in this area of the body reaches 84% (Kass et al 2003). Although the size of the tumor did not influence the outcome of surgical treatment in one study it seems that smaller sarcomas much more often allow for complete resection (Romanelli et al 2008). The present study has revealed that medical diagnosis of FISS is commonly obtained in advanced stage, because in more than 35% of cases a diameter of the tumor was longer than 5 cm, and only 25% of tumors were considered to be small (diameter shorter than 2 cm).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Fortunately, the situation in Poland is better than, for example, in the UK where the most affected site is still the interscapular region and the percentage of FISS arisen in this area of the body reaches 84% (Kass et al 2003). Although the size of the tumor did not influence the outcome of surgical treatment in one study it seems that smaller sarcomas much more often allow for complete resection (Romanelli et al 2008). The present study has revealed that medical diagnosis of FISS is commonly obtained in advanced stage, because in more than 35% of cases a diameter of the tumor was longer than 5 cm, and only 25% of tumors were considered to be small (diameter shorter than 2 cm).…”
Section: Discussionmentioning
confidence: 97%
“…However, we decided to compare histopathological picture of randomly selected cases of FISS with tumors growing in location that allow to excluded their connection with injections. In eariler studies microscopic features of vaccine-associated sarcomas rather than injection site sarcomas were usually described (Couto et al 2002, Gobar and Cass 2002, Romanelli et al 2008. Previous investigations have shown that the most common histological type of FISS is fibrosarcoma; it accounts for about 80-90% of these tumors (Couto et al 2002, Romanelli et al 2008, Giudice et al 2010, Wilcock et al 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,31 The decision of whether to use an adjunctive therapy is often based on histologic grading of the neoplasm. 7 The most widely used grading scale is that described by Kuntz et al for soft tissue sarcomas in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…The obtainment of clean surgical margins is considered important for predicting local recurrence of FISS (Kobayachi et al, 2002;Giudice et al, 2010). But there are reports of up to 50% recurrence rates in neoplasms excised with clear surgical margins (Romanelli et al, 2008;Phelps et al, 2011). This high recurrence rate can be explained by an asymmetrical dissemination of neoplastic cells, hindering accurate margin assessment (Giudice et al, 2010;Ehrhart & Powers, 2013).…”
Section: Discussionmentioning
confidence: 99%